2020
DOI: 10.33365/ts.v18i2.676
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Jokowi’s Commissive Speech Acts in 2014 and 2019 Inaugural Address: A Pragmatic Study

Abstract: This article attempted to identify and describe the commissive acts in the inaugural addresses delivered by the Indonesian president Joko Widodo in 2014 and 2019. This includes the felicity condition of the addresses. The differences between commissive speech acts produced in his inauguration address and the second terms were also contrasted. The data were the transcripts of the addresses in both terms. Descriptive qualitative was implied in this study. The results found that there were two categories of commi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…Therefore, OU is freer to present more commissive acts such as promises, guarantees, and offers in its prospectus. Moreover, according to Firdaus et al (2020), speakers use commissive acts in large numbers to maintain the audience's trust.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, OU is freer to present more commissive acts such as promises, guarantees, and offers in its prospectus. Moreover, according to Firdaus et al (2020), speakers use commissive acts in large numbers to maintain the audience's trust.…”
Section: Discussionmentioning
confidence: 99%
“…Studies related to this research topic have been done previously. Such as studies on commissive acts by Firdaus et al (2020), who identified and described the commissive acts found in the inaugural speeches by the Indonesian president Joko Widodo. Mulatsih et al (2021) examined politeness in commissive speech acts contained in the film's conversation.…”
Section: Introductionmentioning
confidence: 99%
“…Example: I guarantee that the Gerindra party will fight corruption. If there is a member of Gerindra who are corrupt, I will put him in prison by myself (Husain et al, 2020) I guarantee, one more time, I guarantee that I will remove them (Firdaus et al, 2020)…”
Section: Acceptmentioning
confidence: 99%
“…However in political speeches, commissive acts dominated the utterances as the politicians promised that the world (reality) fit their words. Firdaus et al, (2020) states that commissive speech acts in political speeches is used as a way to manipulate public opinions. Mohammed Hashim (2015) studied John Kerry's speech in presidential campaign in 2004 and George Bush inaugural address in 2001.…”
Section: Introductionmentioning
confidence: 99%